Theory of optical transitions in conjugated polymers. II. Real systems. - Marcus, M; Tozer, O; Barford, W (American Institute of Physics Inc., 2014)
The theory of optical transitions developed in Barford and Marcus ["Theory of optical transitions in conjugated polymers. I. Ideal systems," J. Chem. Phys. 141, 164101 (2014)] for linear, ordered polymer chains is extended in this paper to model conformationally disordered systems. Our key result is that in the Born-Oppenheimer regime the emission intensities are proportional to S(1)/⟨IPR⟩, where S(1) is the Huang-Rhys parameter for a monomer. ⟨IPR⟩ is the average inverse participation ratio for the emitting species, i.e., local exciton ground states (LEGSs). Since the spatial coherence of LEGSs determines the spatial extent of chromophores, the significance of this result is that it directly relates experimental observables to chromophore sizes (where ⟨IPR⟩ is half the mean chromophore size in monomer units). This result is independent of the chromophore shape, because of the Born-Oppenheimer factorization of the many body wavefunction. We verify this prediction by density matrix renormalization group (DMRG) calculations of the Frenkel-Holstein model in the adiabatic limit for both linear, disordered chains and for coiled, ordered chains. We also model optical spectra for poly(p-phenylene) and poly(p-phenylene-vinylene) oligomers and polymers. For oligomers, we solve the fully quantized Frenkel-Holstein model via the DMRG method. For polymers, we use the much simpler method of solving the one-particle Frenkel model and employ the Born-Oppenheimer expressions relating the effective Franck-Condon factor of a chromophore to its inverse participation ratio. We show that increased disorder decreases chromophore sizes and increases the inhomogeneous broadening, but has a non-monotonic effect on transition energies. We also show that as planarizing the polymer chain increases the exciton band width, it causes the chromophore sizes to increase, the transition energies to decrease, and the broadening to decrease. Finally, we show that the absorption spectra are more broadened than the emission spectra and that the broadening of the absorption spectra increases as the chains become more coiled. This is primarily because absorption occurs to both LEGSs and quasi-extended exciton states (QEESs), and QEES acquire increased intensity as chromophores bend, while emission only occurs from LEGSs.